Horticultural Agribusiness Development Strategy Based on Technological Innovation in the Digital Era - Tambunan, Lion Fernando (Cattleya Darmaya Fortuna, 2025)
The horticultural agribusiness sector plays a crucial role in providing nutritious food and increasing farmers' incomes. However, the challenges of globalization, climate change, and modern market demands necessitate innovation in production and marketing systems. This study aims to analyze horticultural agribusiness development strategies based on technological innovation in the digital era. The research method employed a descriptive qualitative approach, incorporating literature studies and field observations in horticultural farmer groups in Central Java. The results indicate that the use of digital technologies such as agricultural e-commerce, precision farming, and crop monitoring applications can improve production efficiency, expand market access, and encourage the creation of added value for products. In conclusion, the integration of digital technology in horticultural agribusiness is a crucial strategy for creating a modern, sustainable, and competitive agricultural system.